2010
DOI: 10.1088/0004-637x/726/2/98
|View full text |Cite
|
Sign up to set email alerts
|

On the Efficiency of the Tidal Stirring Mechanism for the Origin of Dwarf Spheroidals: Dependence on the Orbital and Structural Parameters of the Progenitor Disky Dwarfs

Abstract: The tidal stirring model posits the formation of dwarf spheroidal galaxies (dSphs) via the tidal interactions between late-type, rotationally-supported dwarfs and Milky Way-sized host galaxies. Using a comprehensive set of collisionless N-body simulations, we investigate the efficiency of the tidal stirring mechanism for the origin of dSphs. In particular, we examine the degree to which the tidal field of the primary galaxy affects the sizes, masses, shapes, and kinematics of the disky dwarfs for a range of dw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
232
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 167 publications
(249 citation statements)
references
References 161 publications
(306 reference statements)
17
232
0
Order By: Relevance
“…For example, the relatively high recession velocity (V g = +100 km s −=1 ) of the gas-poor isolated dwarf Tucana (Fraternali et al 2009) may indicate that it has been ejected to large distances by a three-body encounter, as envisaged by Sales et al (2007). Such a scenario cannot be invoked in the case of VV124, which has a much smaller galactocentric velocity (V g = +17 km s −=1 ; see also D'Onghia et al 2009;Kazantzidis et al 2011, for other scenarios for the transformation of dwarf galaxies and discussion).…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the relatively high recession velocity (V g = +100 km s −=1 ) of the gas-poor isolated dwarf Tucana (Fraternali et al 2009) may indicate that it has been ejected to large distances by a three-body encounter, as envisaged by Sales et al (2007). Such a scenario cannot be invoked in the case of VV124, which has a much smaller galactocentric velocity (V g = +17 km s −=1 ; see also D'Onghia et al 2009;Kazantzidis et al 2011, for other scenarios for the transformation of dwarf galaxies and discussion).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…All the values of surface brightness are corrected for extinction. Mayer et al (2006Mayer et al ( , 2007 explicitly postulates dwarf disk galaxies as the progenitors of dSphs (see Kazantzidis et al 2011, for a recent and thorough discussion). Indeed, observational evidence of the existence of the expected intermediate stages of such transformation process is beginning to emerge, from study of various environments (see, for example, the disky dEs identified in the Virgo cluster by Lisker et al 2007).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Interactions of galaxies with the potential of larger objects have proved capable of transforming their morphology and kinematics on various scales: those of dwarf galaxies orbiting the Milky-Way-like galaxy (Mayer et al 2001;Kazantzidis et al 2011), galaxies in groups (Villalobos et al 2012), and clusters (Mastropietro et al 2005;Bialas et al 2015). One of the factors influencing the final outcome of such a process is the initial inclination of the galaxy disk with respect to its orbit (Villalobos et al 2012;Łokas et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Internal mechanisms -such as gas consumption via star formation or feedback effects -appear to be insufficient to completely cease the star formation activity in dwarf galaxies. External processes need therefore to be invoked, and they most likely involve a combination of tidal and gas-stripping mechanisms (e.g., Mayer et al 2001bMayer et al ,a, 2006Grebel et al 2003;Peñarrubia et al 2008;Kazantzidis et al 2011). One might argue that the fact that quiescent lowmass galaxies are found out to projected distances larger than 1 Mpc -corresponding to several virial radii for haloes hosting L L * galaxies -is not consistent with the importance of environmental effects.…”
Section: Environmentmentioning
confidence: 99%